Chlorothalonil biotransformation by cytochrome P450 monooxygenases in Sclerotinia homoeocarpa. Issue 19 (3rd September 2018) - Green, Robert; Sang, Hyunkyu; Im, Jeongdae; Jung, Geunhwa
Abstract: Cytochrome P450s have been shown to play a vital role in the xenobiotic detoxification system of Sclerotinia homoeocarpa, the causal agent of the turfgrass disease dollar spot. A previous study indicated that three CYP450s were validated to play a functional role in resistance against different fungicide classes including propiconazole and plant growth regulator, flurprimidol. In this study, we present these CYP450s possess the capability to modify the multi-site mode of action fungicide chlorothalonil. Chlorothalonil is an extensively used contact fungicide and has been shown to persist in soils. High Performance Liquid Chromatography (HPLC) indicated faster rates of chlorothalonil biotransformation by CYP561 and CYP65 overexpression strains when compared to the wild-type and CYP68 overexpression strain. Our GC-MS results show that the primary transformation intermediate found in soils, 4-hydroxy-2, 5, 6 trichloro-isophthalonitrile is produced by CYP450s' metabolism. These findings suggest fungal CYP450s can biotransform chlorothalonil for biodegradation or detoxification. Abstract : Cytochrome P450 monooxygenases from a fungal turfgrass pathogen can biotransform the widely used fungicide chlorothalonil for degradation or detoxification.